About Some Children’s Education in the Spirit of International Concord - B. Boltaev (International Journal of Advanced Science and Technology, 2020)
This article provides a brief overview of the idea of interethnic harmony, the policy of implementing this idea in our country, and the content of some issues in the spirit of interethnic harmony of f